Investigation of Waste Paper Cellulosic Fibers Utilization into Cement Based Building Materials - Viola Hospodarova; Nadezda Stevulova; Jaroslav Briancin; Katarina Kostelanska (Buildings, 2018)
Recently, the utilization of renewable natural cellulosic materials, such as wood, plants, and waste paper in the preparation of building materials has attracted significant interest. This is due to their advantageous properties, low environmental impact and low cost. The objective of this paper is to investigate the influence of recycled cellulosic fibers (in the amount 0.5 wt % of the filler and binder weight) and superplasticizer (in the amount 0.5 wt % of the cement weight) on the resulting properties of cement composites (consistency of fresh mixture, density, thermal conductivity, and compressive and flexural strength) for hardening times of 1, 3, 7, 28, and 90 days. Plasticizer use improved the workability of fresh cement mixture. In comparison to the reference sample, the results revealed a decrease in density of 6.8% and in the thermal conductivity of composites with cellulosic fibers of 34%. The highest values of compressive (48.4 MPa) and flexural (up to 7 MPa) strength were achieved for hardened fiber cement specimens with plasticizer due to their significantly better dispersion of cement particles and improved bond strength between fibers and matrix.